Antibacterial Activity of Endophytic Bacterial Isolates from Kaempferia galanga Leaves - Rafifa Ridha; Dira Hefni; Zetryana Puteri Tachrim; Gian Primahana; Jepri Agung Priyanto; Linosefa Linosefa; Adrial Adrial; Endrinaldi Endrinaldi; Muhammad Eka Prastya (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Indonesia has a high biodiversity, which can be relied upon as a potential source of medicinal materials. One of the medicinal plants in Indonesia is Kaempferia galanga, which demonstrates various pharmacological properties, including antibacterial, anti-inflammatory, antioxidant, anticancer, and antiangiogenic effects. However, directly extracting active compounds from plants requires a considerable amount of biomass. To address this challenge, utilizing endophytic bacteria associated with these plants presents a promising alternative. Consequently, the antibacterial activity of endophytic bacterial isolates from K. galanga leaves needs to be investigated. This study is an experimental laboratory investigation conducted in vitro. Two isolates demonstrated antibacterial activity: isolate code DR4 inhibited the growth of Escherichia coli (3 ± 0.5 mm), while isolate DR10 inhibited the growth of four bacteria: Bacillus subtilis (5 ± 0 mm), Staphylococcus aureus (1.5 ± 0.5 mm), Escherichia coli (1 ± 0 mm), and Pseudomonas aeruginosa (1 ± 0 mm). Disc diffusion tests using ethyl acetate extracts of isolate DR10 showed the highest antibacterial activity at a concentration of 10,000 ppm. The Minimum Inhibitory Concentration (MIC) was determined to be 156.2 ppm against B. subtilis, while the Minimum Bactericidal Concentration (MBC) was >625 ppm. Molecular identification showed that isolate DR 10 had 100% similarity to Bacillus sp. TS8. The active compound suspected to have antibacterial properties is pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl)-, with the highest abundance.